Analisis Penerapan Prinsip-Prinsip Ekonomi Syariah pada Pedagang di Taman Merdeka Kota Manna Kabupaten Bengkulu Selatan - Emelia Kontesa; Nurul Hak; Padlim Hanif (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to understand the application of Islamic economic principles in trading activities at Taman Merdeka, Kota Manna, and to identify the factors influencing the implementation of these principles in the trading activities at Taman Merdeka, Kota Manna. The method employed in this study is a qualitative approach, with data collection conducted through observation, interviews, and documentation. Data analysis is performed using the Miles and Huberman model.This study analyzes the application of Islamic economic principles among traders at Taman Merdeka, Kota Manna. The findings indicate that traders generally have implemented Islamic economic principles, such as honesty, justice, and avoidance of usury, although their theoretical understanding of these concepts remains limited. The application of these principles is supported by religious awareness, business ethics, a culture of solidarity, as well as supervision and communication among business actors. However, traders also face challenges, such as economic pressure and a lack of understanding of Islamic economic terminology. Nevertheless, they remain committed to maintaining honesty and viewing trading activities as a form of worship in order to achieve blessings in their endeavors.